Apologies as Signals: With Evidence from a Trust Game - Ho, Benjamin (Management Science, 2012)
Apologies are part of a social institution designed to restore frayed relationships not only in daily life but also in the domains of corporate governance, medical malpractice litigation, political reputation, organizational culture, etc. The theory shows that in a general class of moral hazard games with imperfect information about agents with two-dimensional type, apologies exhibit regular properties—e.g., apologies are more frequent in long relationships, early in relationships, and between better-matched partners. A variant of the trust game demonstrates that communication matters in a manner consistent with economic theory; specifically, the words “I am sorry” appear to select equilibrium behavior consistent with the theory's main predictions. This paper was accepted by Brad Barber, Teck Ho, and Terrance Odean, special issue editors.